Inequalities in referral pathways for young people accessing secondary mental health services in south east London. - Chui, Zoe; Gazard, Billy; MacCrimmon, Shirlee; Harwood, Hannah; Downs, Johnny; Bakolis, Ioannis; Polling, Catherine; Rhead, Rebecca; Hatch, Stephani L. (European Child & Adolescent Psychiatry, 2021)
Differences in health service use between ethnic groups have been well documented, but little research has been conducted on inequalities in access to mental health services among young people. This study examines inequalities in pathways into care by ethnicity and migration status in 12–29 years old accessing health services in south east London. This study analyses anonymized electronic patient record data for patients aged 12–29 referred to a south east London mental health trust between 2008 and 2016 for an anxiety or non-psychotic depressive disorder (n = 18,931). Multinomial regression was used to examine associations between ethnicity, migration status, and both referral source and destination, stratified by age group. Young people in the Black African ethnic group were more likely to be referred from secondary health or social/criminal justice services compared to those in the White British ethnic group; the effect was most pronounced for those aged 16–17 years. Young people in the Black African ethnic group were also significantly more likely to be referred to inpatient and emergency services compared to those in the White British ethnic group. Black individuals living in south east London, particularly those who identify as Black African, are referred to mental health services via more adverse pathways than White individuals. Our findings suggest that inequalities in referral destination may be perpetuated by inequalities generated at the point of access.